Comparative assessment of fetomaternal outcome in twin pregnancy with singleton pregnancy at tertiary care centre - Gupta, Divya; Mital, Premlata; Meena, Bhanwar Singh; Benwal, Devendra; Saumya, .; Singhal, Sunita; Ainani, Richa (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Multiple pregnancy remains one of the highest risk situations for the mother, foetus and neonate despite recent advances in obstetrics, perinatal and neonatal care. Twin pregnancies have increased rates of obstetric and perinatal complications compared to singletons Objective of present study was comparative assessment of fetomaternal outcome in twin pregnancy with singleton pregnancy in Obstetrics and Gynaecology Department of S.M.S. Medical College, Jaipur. Methods: This was a hospital based, prospective observational study done in the Department of Obstetrics and Gynaecology. S.M.S. Medical College, Jaipur from April 2015 to March 2016. 150 women with twin pregnancy and 150 women with singleton pregnancies at gestation age of 28 weeks and above coming for delivery and consented for the study were included in the study. Women with chronic medical disorder or chronic hypertension were excluded from the study. Maternal and neonatal outcome recorded and analysed. Results: Occurrence of twin in our study was 2.82%. Risk of preterm labour was about nine times higher in twin pregnancies than the singleton (OR: 2.74, 95% CI; 1.4494-5.1884, P value 0.001). The risk of premature rupture of membrane was increased by 2.74 times in twin pregnancies (OR:2.74; 95% CI: 1.4494-5.1884, p value .001). There was 3-time increased risk of malpresentation (OR 3.14; CI:1.7184-5.7480, p value .00002) and 2.28 times increase in hypertensive disorder (OR 2.28; 95% CI: 1.0727-4.8823, p value .03) in twin pregnancies. The risk of asphyxia and septicaemia was 2.5 times more in twins. Conclusions: Twin pregnancy is a high-risk pregnancy with more complications in mother and foetus and is a great challenge for obstetrician. So, it should be managed carefully at tertiary care centre to reduce the maternal and perinatal mortality and morbidity.